Recognizing biography - Epstein, William H. (Philadelphia : University of Pennsylvania Press, 1987)
Epstein's narrative interweaves interpretive and theoretical chapters as it emplots the discourse of English biography from Walton to Strachey. In this way familiar generic relationships between biographer, subject, life, text, falsehood, and readership are analyzed in specific (if constantly shifting) historical, literary, cultural, and economic texts.
Frontmatter -- Content -- Acknowledgments -- 1. Introduction: Recognizing Biography -- 2. Altering the Life-Text: Walton's Life of Donne -- 3. Recognizing the Life-Text -- 4. Patronizing the Biographical Subject: Johnson's Life of Savage -- 5. Recognizing the Biographical Subject -- 6. Recognizing the Biographer: Boswell's Life of Johnson -- 7. Recognizing the Life-course: Strachey's Eminent Victorians -- Notes -- Index
Includes bibliographical references (pages 173-214) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: English prose literature -- History and criticism; Biography as a literary form; Biography; Biographies as Topic; Biographie (Genre littéraire); Prose anglaise -- Histoire et critique; Biographies; biographies (literary works); biography (general genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM / Semiotics & Theory; Biography as a literary form; English prose literature; Biografieën.; Engels; Prose anglaise -- Histoire et critique; Biographie (genre littéraire); Criticism, interpretation, etc